Socialization and Counseling of Sharia Cooperatives in Tulusayu Village on The Existence of Kanindo Syariah Cooperative - Amaliyah, Angguliyah Rizqi; Mauludyah, Afiatul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The purpose of this study is to explore the role of Sharia Cooperatives, a part of Sharia Financial Institutions, in improving community welfare. These institutions operate on sharia principles, aiming to generate profits for both customers and financial institutions. The study focuses on the impact of these cooperatives on rural communities, such as Tulusayu Village in Wagir District, Malang Regency, who require funds to develop their economy. Method: The study employs socialization and counseling as methods to educate the people of Tulusayu Village about the characteristics, principles, economic goals, and products of Sharia Cooperatives. The focus is on the development of small micro businesses, particularly through the Kanindo Syariah JATIM Cooperative Wagir Branch. Practical Applications: The practical application of this study lies in its potential to provide the community with knowledge and understanding about the existence and benefits of Sharia Cooperatives. By participating in socialization and counseling activities, the community can learn how to leverage these cooperatives for economic development. Conclusion: The study concludes that the active participation of the community in these activities can significantly support the improvement of the economy in Tulusayu Village. The existence of Sharia Cooperatives, therefore, plays a crucial role in community development and welfare improvement.